2015
DOI: 10.1007/s10529-015-1881-6
|View full text |Cite
|
Sign up to set email alerts
|

A MALDI-MS-based quantitative targeted glycomics (MALDI-QTaG) for total N-glycan analysis

Abstract: This MALDI-MS-based glycomics technology has wide applications in many clinical and bioengineering fields requiring sensitive, quantitative and fast N-glycosylation validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The sialoglycoproteins are first modified using acetohydrazide, followed by enzymatic releasing. The reducing ends of both neutral and acidic glycans are then derivatized by 2‐aminobenzoic acid (2‐AA) or Girard's reagent P . Another approach that can label sialic acids at a protein level is performed in the presence of EDC using p ‐toluidine instead of acetohydrazide .…”
Section: Oligosaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The sialoglycoproteins are first modified using acetohydrazide, followed by enzymatic releasing. The reducing ends of both neutral and acidic glycans are then derivatized by 2‐aminobenzoic acid (2‐AA) or Girard's reagent P . Another approach that can label sialic acids at a protein level is performed in the presence of EDC using p ‐toluidine instead of acetohydrazide .…”
Section: Oligosaccharidesmentioning
confidence: 99%
“…The sialoglycoproteins are first modified using acetohydrazide, followed by enzymatic releasing. The reducing ends of both neutral and acidic glycans are then derivatized by 2-aminobenzoic acid (2-AA) or Girard's reagent P. [248][249][250] Another approach that can label sialic acids at a protein level is performed in the presence of EDC using p-toluidine instead of acetohydrazide. 247,251,252 In combination with stable isotope labeling, the method has been used for the quantitative analysis of sialoglycans from cells treated with metabolic label, showing its potential in metabolic glycoengineering.…”
Section: Amidationmentioning
confidence: 99%
“…Recently, our group has reported MALDI-MS-based quantitative analysis of carbohydrates and bioactive lipids ( e.g ., N-acyl homoserine lactones) that have an aldehyde or ketone group 34 35 36 . Previous studies have demonstrated that chemical derivatization of the target molecules could dramatically enhance the sensitivity (up to 6 × 10 4 times) and allow more accurate quantitative analysis using only MALDI-MS without prior sample purification 36 .…”
Section: Resultsmentioning
confidence: 99%
“…To address these problems, matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS), which is an extremely sensitive and robust method that is suitable for the analysis of complex mixtures, could be a great alternative tool for the analysis of endogenous estrones 34 35 . Here, we demonstrate a MALDI-based quantitative platform for the quantitation of endogenous estrogenic hormones in human body fluid and cells ( Fig.…”
mentioning
confidence: 99%
“…Kim and collaborators evaluated the performance of a quantitative MALDI targeting glycomics approach, in the analysis of N -glycans, in both, purified AFP from normal cord blood (control condition) and from HCC cell line—Huh7 cells—(increase of core-fucosylation). It was demonstrated that the results are promising in clinical and bioengineering fields ( 110 ). In 2009, Lattová and collaborators examined serum of animal models with HCC-inducted through MALDI-MS, identifying forty different N -glycans, in which some structures appeared to have highest frequency in HCC samples ( 29 ).…”
Section: Mass Spectrometry (Ms) As a Tool For Glycomics Analysismentioning
confidence: 99%